2012
DOI: 10.1016/j.molcel.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

R-Loop Formation Is a Distinctive Characteristic of Unmethylated Human CpG Island Promoters

Abstract: Summary CpG islands (CGIs) function as promoters for approximately 60% of human genes. Most of these elements remain protected from CpG methylation, a prevalent epigenetic modification associated with transcriptional silencing. Here, we report that methylation-resistant CGI promoters are characterized by significant strand asymmetry in the distribution of guanines and cytosines (GC skew) immediately downstream from their transcription start sites. Using innovative genomics methodologies, we show that transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
1,046
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 718 publications
(1,119 citation statements)
references
References 65 publications
72
1,046
0
1
Order By: Relevance
“…To test this model, we assayed R-loop formation genome-wide in SH-SY5Y cells expressing the control or SMN shRNA using DNA-RNA immunoprecipitation (IP) sequencing (DRIPseq), which enriches for hybrid structures in the chromatin using the R-loop-specific antibody S9.6 (44). We also performed DRIPseq on samples immunoprecipitated with mouse IgG as a control for specific enrichment.…”
Section: Smnmentioning
confidence: 99%
“…To test this model, we assayed R-loop formation genome-wide in SH-SY5Y cells expressing the control or SMN shRNA using DNA-RNA immunoprecipitation (IP) sequencing (DRIPseq), which enriches for hybrid structures in the chromatin using the R-loop-specific antibody S9.6 (44). We also performed DRIPseq on samples immunoprecipitated with mouse IgG as a control for specific enrichment.…”
Section: Smnmentioning
confidence: 99%
“…61,62 In contrast, R-loops play beneficial roles by mediating CRISPR interference, 63,64 promoting IgG class switching, 65,66 and by regulating transcription. 67,68 These structures can form in cis 60 or trans 69 in vivo, either by "threading back" of nascent RNAs during transcription by RNA Pol II, through the action of the homologous recombination machinery, or associated RNA-binding proteins as in the case of CRISPR. 60,70,71 Given that RNP assembly defects cause R-loops, 60,70 we speculated that loss of DBP2 might promote formation of these structures between the GAL lncRNAs and GAL gene promoters.…”
mentioning
confidence: 99%
“…R-loops have been suggested to play a key role in preventing DNA methylation at CGI. 36 Our group has recently shown that GC skew additionally defines key points of RNAP II pausing in CGI promoters, 37 regulating its release into elongation. In previous work, we showed that the re-establishment and persistence of RNAP II, even in its paused state impedes remethylation and gene re-silencing after DAC-induced demethylation.…”
Section: Discussionmentioning
confidence: 99%